(untitled) (EUROPEAN AND ASIAN LAW REVIEW, 2024)
At the present stage, the Russian Federation and the member states of the Eurasian Economic Community care about the welfare of families with children, and appropriate changes are being made to legislation. An example of this would be a change in legislation - the introduction of a universal allowance for families with children, as a new social provision in the Russian Federation. The article analyzes the legislation regulating the provision of state benefits to families with children in the EAEU countries, identifying similarities and differences in the legal regulation of the assignment and payment of benefits to families with children.